The Relationship Between Psychological Well-Being and Autonomy in Young People According to Age - De-Juanas, Ángel; Bernal Romero, Teresita; Goig, Rosa (Frontiers in Psychology, 2020)
Psychological wellbeing manifests itself in all aspects of human activity and is essential to understanding whether young people experience life satisfaction and whether, as they mature, wellbeing can be associated with different levels of personal autonomy. This quantitative study was developed within the framework of international research on young people’s autonomy in the transition to adulthood. Its main objectives were to analyze the relationship between psychological wellbeing and autonomy and examine potential variations between the two variables according to age. To this end, Ryff’s Psychological Wellbeing Scale and the Transition to Adulthood Autonomy Scale (EDATVA) designed by Bernal et al. were used with a sample of 1,148 young people aged 16-21 from Madrid, Spain and Bogotá, Colombia. The results show that almost all the dimensions on the Psychological Wellbeing Scale correlate significantly and positively with the dimensions on the EDATVA scale. Specifically, moderate correlations were obtained between self-organization on the EDATVA scale and purpose in life (r=.568; p=.01) and environmental mastery (r=.447; p=.01) on the Psychological Wellbeing Scale. In turn, autonomy on Ryff’s scale obtained the highest correlation (r=.382.; p=.01) with understanding context on the EDATVA scale. It was also found that the older 18-21 age group obtained higher scores than the younger 16-17 age group in all the dimensions on both the EDATVA and the Psychological Wellbeing Scale. Earlier studies endorse the results found in this research, especially the differences in the scores for both scales according to age groups. This opens avenues for future research to analyze the relationship between psychological wellbeing and autonomy as independent variables in other sectors of the population.